Meningkatkan Kreativitas dan Kepedulian Lingkungan Siswa MI Nurul Falah Bondowoso Melalui Pemanfaatan Sampah Anorganik - Gilang Ramadhan; Rahmat Wijaya; Najwa Dwi Galuh Ardillah; Wahyu Bintang Firmansyah; Nuraida Solle; Belkis Izatus Sahwa; Dimas Bastara Zahrosa; Agung Nugroho Puspito (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
Low environmental awareness and lack of learning interest among students at MI Nurul Falah were identified, largely due to a curriculum dominated by purely theoretical instruction without practical application. This community engagement project aimed to address these issues by enhancing students' creativity, environmental concern, and basic academic skills through the utilization of inorganic waste. This social service activity was conducted over three weeks, focusing on 4th-grade students at MI Nurul Falah, using the Project-Based Learning (PBL) approach. Data were collected through observation (activities and environmentally conscious behavior), tests (ecological knowledge via pre-test and post-test), and questionnaires. Data analysis was performed using descriptive qualitative and quantitative methods. A significant improvement was found across all measured aspects. Quantitatively, students' ecological knowledge increased from 40% on the pre-test to 90% on the post-test. Qualitatively, positive behavioral changes were noted, characterized by increased student responsibility in performing cleanup duty and tangible practices in maintaining school cleanliness. Student creativity also increased through plastic waste recycling into crafts. This success demonstrates the effectiveness of the PBL approach in holistically integrating creativity, environmental awareness (3R principles), and basic academic skills. The program serves as a model for a holistic educational initiative. A limitation of this program is its short duration (three weeks). The program is expected to be continued and adapted by the MI Nurul Falah educators.